2020
DOI: 10.1111/1440-1703.12186
|View full text |Cite
|
Sign up to set email alerts
|

Geographical personality gradient in herbivorous animals: Implications for selective culling to reduce crop damage

Abstract: Traditional lethal techniques used to mitigate wildlife damage have targeted entire populations through the use of random harvesting. However, recent literature has suggested that controlling population size by random harvesting is not the only mean to mitigate human-wildlife conflicts. Controlling problem individuals may also be important because individuals with behavioral charac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Therefore, it was difficult to separate the effects of each stimulus. However, we assumed that we could detect differences in escape responses even with the combined stimuli, given that previous studies reported that the boldness of sika deer ( Cervus nippon ) could be detected with a visible flash camera (Honda 2021), and that vehicle traffic frequency affected the behavioral patterns of carnivores (Watabe and Saito 2021b). During the survey, we continuously illuminated the individual animal and recorded whether it escaped in 10s or 60s.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it was difficult to separate the effects of each stimulus. However, we assumed that we could detect differences in escape responses even with the combined stimuli, given that previous studies reported that the boldness of sika deer ( Cervus nippon ) could be detected with a visible flash camera (Honda 2021), and that vehicle traffic frequency affected the behavioral patterns of carnivores (Watabe and Saito 2021b). During the survey, we continuously illuminated the individual animal and recorded whether it escaped in 10s or 60s.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, variations in personality of forest animals is important as they influence their dispersal to open land, especially out of the forest (Sol et al 2013). Recent studies have shown that urban wildlife is bolder than its rural counterpart (Møller 2008; Evans et al 2010; Sih et al 2012; Lowry et al 2013; Gendall et al 2015) and that there is a personality (boldness) gradient from farmland to a deep forest (Honda 2020). These bold and exploratory personality traits are considered together as invasion syndrome (Chapple et al 2012; Merrick and Koprowski 2017).…”
Section: Personalitymentioning
confidence: 99%